COX-2 induces T cell accumulation and IFN-γ production during the development of chromium allergy. (18th August 2019) - Sitalaksmi, Ratri Maya; Ito, Koyu; Ogasawara, Kouetsu; Suto, Yoshiko; Itabashi, Madoka; Ueda, Kyosuke; Hirasawa, Noriyasu; Narushima, Takayuki; Hendrijantini, Nike; Kresnoadi, Utari; Sasaki, Keiichi
Abstract: Chromium (Cr) is commonly added into various metal alloys to improve some mechanical properties such as corrosion resistance, strength, and workability. However, Cr is also known to be a metal allergen for some individuals. Metal allergy is a T cell-mediated disease with symptoms of inflammation and swelling that involve inflammatory cytokines and prostaglandins. Hence, suppressing these inflammation paths by using COX-2 inhibitor might be useful in treating Cr allergy. In this study, mice were used with Cr-induced allergy challenge model. The mice were injected with celecoxib once per day for 7 days one hour after the challenge. Footpad samples were stained with haematoxylin and eosin (H&E), and lymphocytes were isolated from popliteal lymph nodes for the flow cytometric analysis. The results show that both prostaglandin E2 (PGE2 ), a known mediator of inflammation, and cyclooxygenases (COX)-2 have important roles in the development of Cr allergy. Further, COX-2 inhibitor, celecoxib, was effective in relieving swelling and inflammation in Cr-allergic mice concordant with suppression of IFN-γ production by CD8 + T cells and T cell accumulation in the lymph nodes. Therefore, the inhibition of COX-2 may be a therapeutic target for Cr allergy, and additional molecules in the PGE2 signalling pathway may also be an effective therapeutic target for the treatment of metal allergy.